Pengaruh Brand Ambasador Dan Kesadaran Merek Terhadap Keputusan Pembelian Di Tokopedia (Studi kasus Mahasiswa Fakultas Ekonomi dan Bisnis Unisma angkatan 2019) - Muhammad Yusril Hafidz; Nurhidayah Nurhidayah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract Tokopedia is Indonesia's largest digital start-up in the trading sector. One of Indonesia's most popular marketplaces is Tokopedia. Progressively well known among general society, Tokopedia has prevailed with regards to turning into a compelling unicorn in Indonesia and Southeast Asia. Repurpose of this study to ascertain and evaluate the impact of Brand Ambassadors and brand awareness on Tokopedia students' purchasing decisions. This study employs quantitative techniques. The populace in this review were Unisma understudies class of 2019, the staff of financial matters and business. Techniques for gathering data through the distribution of questionnaires Using the Lemeshow formula and a purposive sampling method, 100 students from the 2019 Faculty of Economics, Unisma, and Business classes provided the sample for this study. The factors in this study were Brand Envoy (X1), Brand mindfulness (X2), and Buy Choice (Y). Instrument test, normality test, classic assumption test, multiple linear regression analysis test, hypothesis test, and coefficient of determination test are the data analysis methods that are utilized with the assistance of SPSS 25 software for Windows. According to the findings of this study,brand ambassadors have a positive and significant effect on buying decisions, and brand awareness is also positively and significantly influenced by brand ambassadors. Additionally, purchasing decisions are significantly influenced by brand awareness. Keywords: Brand ambassador, Brand awareness and Purchase decision